2018
DOI: 10.14390/jsshp.hrp2018-001
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the effectiveness of metreurynters for balloon tamponade

Abstract: Aim: Several devices are used for balloon tamponade. In Japan, metreurynters are widely used for cervical ripening; however, there is little evidence for their use in hemostatic uterine balloon tamponade. This study aimed to assess the non-inferiority of metreurynters as the balloon device for obstetric hemorrhage. Methods: Medical charts of all patients with obstetric hemorrhage of more than 1,000 ml who underwent balloon tamponade with metreurynters were retrospectively reviewed for five years at a tertiary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

5
1

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…Bleeding points were assessed a few minutes after administering Sonazoid. A Fuji-Metro balloon (Fuji Latex, Tokyo, Japan), 24 originally designed for cervical ripening before inducing labor, was then inserted at the bleeding point in the uterine cavity and inflated until extravasation ceased. The off-label use of the Fuji-Metro balloon was approved by the Juntendo University Hospital Ethics Committee (#18-040).…”
Section: Methodsmentioning
confidence: 99%
“…Bleeding points were assessed a few minutes after administering Sonazoid. A Fuji-Metro balloon (Fuji Latex, Tokyo, Japan), 24 originally designed for cervical ripening before inducing labor, was then inserted at the bleeding point in the uterine cavity and inflated until extravasation ceased. The off-label use of the Fuji-Metro balloon was approved by the Juntendo University Hospital Ethics Committee (#18-040).…”
Section: Methodsmentioning
confidence: 99%
“…Recent studies have shown the success rates of hemostasis to be in the range of 86-93.9%; success rates in our clinical experience are also high, at approximately 93.9%. 19) A clinical comparison of results obtained before and after the introduction of balloon tamponade revealed a decrease in the frequency of employing surgical hemostatic procedures and TAE in cases of vaginal delivery, indicating the effectiveness of balloon tamponade. 17) Currently, balloon tamponade is recommended in the guidelines of the World Health Organization (WHO) and by major academic societies such as the International Federation of Gynecology and Obstetrics (FIGO), American College of Obstetricians and Gynecologists (ACOG), Royal College of Obstetricians and Gynecologists (RCOG), and Society of Obstetricians and Gynaecologists of Canada (SOGC).…”
Section: Uterine Balloon Tamponadementioning
confidence: 99%
“…14) Even in cases of massive hemorrhage associated with cervical pregnancy in early gestation or ectopic pregnancy in a cesarean section scar, placement of a uterine cervix dilation balloon (Minimetro, Soft Medical Co., Ltd.; Cook double balloon, Tokibo Co., Ltd.), with infusion of a small amount (15-40 ml) of physiological saline, has proven to be effective. 19) However, balloon tamponade can be problematic as the balloon may become dislodged from the uterus, and blindly pressing on the bleeding point may fail to achieve hemostasis. To solve these problems, infusion of water into the balloon while confirming the bleeding point with an ultrasonic contrast agent has been proposed.…”
Section: Uterine Balloon Tamponadementioning
confidence: 99%
“…This is a hemostatic technique used for overall uterine hemorrhage in the puerperal period including atonic bleeding, incomplete cervical laceration, crush syndrome, and bleeding from the separation surface of placenta previa. Balloon tamponade is also effective and useful for uterine hemorrhage from CSP and cervical pregnancy (Figure 4) [46]. In an emergency, insertion and placement of the balloon are technically easy and can be performed expeditiously; this technique is simple and minimally invasive.…”
Section: Balloon Tamponadementioning
confidence: 99%
“…Then, ultrasoundguided D&C to evacuate the gestational sac is performed a week later after MTX therapy. Bleeding point during D&C could be found by contrast-enhanced ultrasonography, and a cervical ripening miniballoon (Minimetro ® ) could be inserted at the bleeding point and inflated until bleeding stops [46,49]. If bleeding continues, TAE or laparoscopic wedge resection would be performed as soon as possible.…”
Section: A Minimally Invasive Hemostatic Strategy In Csp and Cervicalmentioning
confidence: 99%